The silenced generation: the “black children” of China’s one-child policy - Wang, Jingxian (2023)
This research illustrates a very little-known social phenomenon of “black children” (hei haizi) who experienced their daily concealment under the one-child policy in China. Challenging existing scholarship of critiquing the state-sanctioned harm against individual families, especially parents’ sufferings and illegal children’s denial status in documents, this research reveals the family as a key figure in distinguishing the “black children” from other “normal” population with the support of state power. It repositions the “black children” as the primary victims of losing their family membership, continued identity, stabilized childhood, reciprocal human respects and freedom in a given society. Details of their lived experiences from day-to-day base was limited touched. The term of “black children” was used to mainly suggest this population’s lack of formal legitimised personhood (hukou registration) in existing studies and documents, however, this research aims at expanding meanings of the label of “black” on levels of formal identity, physical presence, and emotional recognition, so we can have a better understanding what “black” really meant (and still means) to them. This research explains why the “black children” were born, how they were concealed in given families and communities, and what impacts left on their sense making of the identity, belonging, and recognition. Narratives of their displaced childhood, discontinued family membership and disruptive recognition signposts my argument of their triple “black identity” constructed throughout: not only the formal denial against the “black children” on the level of abstract legitimacy, but also family exclusion and social alienation. Furthermore, this generation was not only silenced by the policy’s coercion and family injustice, but also doubly muted by the rapid policy changes in modern China.